Penerapan Disiplin Kerja Dalam Meningkatkan Kinerja Pegawai Pada PT. Vanesa Sukma Mandiri - Andrean, Rio; Suroso, Suroso; Wijaya, Muhammad Adhimawan (Jurnal Mirai Management, 2025)
Work discipline is an attitude of respecting, obeying, and complying with regulations that are considered as responsibilities. Human resources are a crucial factor for the success of a company in achieving its goals. This study aims to identify and analyze the implementation of work discipline at PT Vanesa Sukma Mandiri. The method used is qualitative research, with data collection techniques through observation and interviews. The population in this study consisted of 18 employees of PT Vanesa Sukma Mandiri, with the need for three informants, namely key, main, and additional informants. The results of the study indicate that the implementation of work discipline in improving the performance of PT Vanesa Sukma Mandiri employees is still lacking, with many employees not paying attention to punctuality of arrival, going home early, and being absent without explanation, which indicates that the level of employee work discipline is not optimal